PSYCHOLOGICAL WELL-BEING OF RUSSIAN AND ARMENIAN STUDENTS: A CROSS-CULTURAL ASPECT - Shipova, N.S.; Rumyantsev, Yu. V.; Samokhvalova, A. G. (Modern Psychology, 2021)
This article presents the results of an empirical analysis of the components of happiness and well-being in accordance with the theoretical and partially empirically verified author’s model. The article describes the results of descriptive statistical processing of data from 363 respondents, as well as factor analysis of data on happiness and well-being in two samples: Russian and Armenian students. Comparison of these indicators is also described. As a result, various ideas about psychological well-being that exist among student youth are highlighted. If there are similarities in considering well-being as a result and goal of activity (the factor "Well- being as a result / activity"), as well as the image of the future (factor "Well-being as a goal"), which a person strives for, students of different nationalities put different ideas into this image. Russians combine family, personal and professional well-being more organically than Armenians. At the same time, Armenians better integrate success in interpersonal and intrapersonal interaction, while Russian students tend to share these parameters. In general, the article illustrates the similarity of quantitative indicators of psychological well-being and happiness in Russian and Armenian students with different qualitative content of the studied indicators.